APOLOGIZING IN ARABIC AND ENGLISH: An Interlanguage Pragmatic Case Study of Students at an Islamic Boarding School in Indonesia - Abdulkhaleq Ali Al-Ra (2020)
The selection and production of appropriate semantic formulas of apologizing for paying off violation of social norms to restore harmony is a hard task. Students of Senior Boarding School in Indonesia find it harder to form appropriate apology formulas in the Arabic and English as non-native languages due to the lack of pragmatic competence. The selection and production of the semantic formulas of apologizing by students of an Islamic Boarding School become the focus of this dissertation, which examines their pragmatic competence in the realization of the apology strategies in the Arabic and English languages. More specifically, this dissertation examines (1) what apology strategies used by Senior Boarding School Students in Arabic and English?, (2) how contextual factors (external vs. internal) influence the students' apologizing?, (3) in what ways Senior Boarding School Students make pragmatic transfer when apologizing in Arabic and English? The participants are 202 students recruited to fill in a DCT, which consists of eight situations about the violation of the rules of the boarding school - utilizing the five semantic formulas of apologizing from Olshtain and Blum-Kulka 1983 (CCSARP). The results show that the students used identical semantic formulas in both languages. They prefer to use the Expression of regret and Promise for Forbearance strategies. The results also reveal that the internal and external factors affect the students' selection and production of the apology strategies in both languages. Besides, the students' pragmatic transfer occurs in linguistic areas like overgeneralization, inappropriateness, and conceptual transfer from L1 to L2. Overall, the students showed low proficiency in the pragmatic competence of the speech acts of apologizing in the English and Arabic, because successful communication is built-in two-way interaction pure of linguistic barriers.